Pengaruh Media Flash Card Terhadap Kemampuan Mengenal Huruf Pada Anak Kelompok A - Nawafilaty, Tawaduddin (JCE is Published by Early Childhood Islamic Education, 2017)
The aim of of this study is to know the influence of flash card media on the ability to recognize letters in children of group A children of Al-Kautsar kindergarten Surabaya. This study uses Pre Experimental Design research by using One Group Pretest - Posttest Design model. The subjects used were group A children amounted to 21 children. Data collection methods used are observation and documentation with data analysis technique using Wilcoxons Signed Rank Test. Based on data analysis obtained by using the Wilcoxons signed rank test obtained tcount = ttable or 7,4396 = 2,704, and Tcount <Ttabel (0 <59), so Ho is rejected and Ha is accepted. Thus, the study hypothesis that reads